Simulations of graphite boronization: A molecular dynamics study of amorphization resulting from bombardment - Rau, Aaditya; Jubin, Sierra; Vella, Joseph R.; Kaganovich, Igor D. (Frontiers in Physics, 2022)
The molecular dynamics code LAMMPS was used to simulate the bombardment of a graphite structure by atomic boron with impact energies ranging from 50–250 eV. The transient structural evolution, penetration depth, and amorphous layer thickness were analyzed. Simulations show that larger impact energies lead to a greater volume of amorphization and penetration of boron, but that the growth rate of the amorphous layer decreases with increasing fluence. Furthermore, the change in surface chemistry of the amorphized structures was studied using the ReaxFF formalism, which found that the amorphization process introduces dangling bonds thus increasing reactivity in the amorphous region.